Modelling and optimization study of electrocoagulation process for fluoride removal using aluminium electrode / Muhammad Afiq Muhaimin Che Hasbullah - Che Hasbullah, Muhammad Afiq Muhaimin (2017)
Electrocoagulation (EC) has been recognized as one of the most popular and widely used process in water and wastewater treatment throughout the world. This research is focusing on the modelling optimization of electrocoagulation for fluoride removal. The objective of this study are to develop mathematical model of the electrocoagulation process for fluoride removal, study the effect of voltage and electrolysis time towards removal efficiency and to obtain the optimum conditions of the electrocoagulation process that lead to maximum fluoride removal using the dynamic optimization technique. A mathematical model was developed and validated with the experimental data. The sensitivity analysis of the proposed model was performed to check the significance parameter towards removal efficiency, which can determine the parameter to be optimized. In the dynamic optimization study, an orthogonal collocation of the finite elements was implemented in the MATLAB® environment using a dynopt code package. The proposed model from the first principle can be considered validated since the average value R2 is 0.99. The result show the percentage removal of fluoride increases as the voltage increase due to the amount of Al3+ions produced. For optimum condition, it is shown that 92.53% percent removal can be achieved with the range of voltage from 11.2 V to 11.9 V at 30 minutes of process time. In a nutshell, the result showed that this EC process can be considered as potential alternative technology for fluoride removal in wastewater.